Sei sulla pagina 1di 48

# ASEN 5050

SPACEFLIGHT DYNAMICS
Two-Body Motion

## Lecture 3: The Two Body Problem 1

Announcements
Homework #1 is due right now!
Either handed in or uploaded to D2L
Late policy is 10% per school day, where a day starts at
9:00 am.

## Lecture 3: The Two Body Problem 2

Space News
Visiting asteroid this Sunday. Maybe 60 feet in diameter?

## Lecture 3: The Two Body Problem 3

Space News
Itll take a small
Visiting asteroid telescope to see it.

Concept Quiz #3

Concept Quiz #3

Concept Quiz #3

Concept Quiz #3

Challenge #2

## For those of you who are very familiar with the

properties of conic sections:

## Consider planar orbits (elliptical, parabolic, hyperbolic)

What do you get if you plot vx(t) vs. vy(t)?

## vy Anyone have a guess,

who didnt email me?

vx
Lecture 3: The Two Body Problem 9
Challenge #2
Anyone who suggested a solution
even remotely similar earned a point.
Circles and circular arcs! Which was 3 people.

Homework #1

## Darn orbital dynamics. The ISS is not cooperative at

the moment. Here are the last and next passes, as
viewed from Boulder:

ISS Passes

ISS Passes

ISS Passes

## Lecture 3: The Two Body Problem 14

Todays Lecture Topics

## Then: More two-body orbital element computations

Our toolbox:
Newtons law of gravitation
v2

r = 3r = Specific Energy
r 2 r
Vis-Viva Equation
2
v= Most everything else comes
r a
Lecture 3: The Two Body Problem
straight from these. 15
Properties of Conic Sections

v e a
2
Ellipses < <0 0e<1 a >0
r
2
Parabolas = =0 e=1 a =
r
2
Hyperbolas > >0 e>1 a<0
r h2
Since = a(1 e 2 ) is positive

Orbital Period

## Last time we proved Keplers 2nd and 3rd laws and

arrived at an expression for the orbital period of an
ellipse:
s
s
a3 km3
P = 2 units = 3 2 = seconds
km /s

Mean Motion

## We also arrived at an expression for the mean motion:

s
n= P = 2
P sec

2 2
n= = q
P 2 a3

r

a3
Lecture 3: The Two Body Problem 18
Where are we in an orbit?
We have:
Our position in an orbit relative to Earth
The time
The true anomaly,

We want to know:
How long it will take to get
somewhere
The time profile of (t) r

determining how much
area is swept out in some
amount of time.

## Lecture 3: The Two Body Problem 19

The Anomalies
The true anomaly,
The actual, measured angle
Notice that this does not advance at a constant rate in an elliptical orbit

Mean anomaly, M
An angle that does
rate in an elliptical orbit.
M = n(t tp )
r

Eccentric anomaly, E
An angle that helps
translate from the true
anomaly to the mean
anomaly

## Lecture 3: The Two Body Problem 20

The Anomalies
The true anomaly,
The actual, measured angle
Notice that this does not advance at a constant rate in an elliptical orbit

Mean anomaly, M
An angle that does
rate in an elliptical orbit.
M = n(t tp )
r

Eccentric anomaly, E E
An angle that helps
translate from the true
anomaly to the mean
anomaly

## Lecture 3: The Two Body Problem 21

The Anomalies
Some quick mental exercises:

## Lecture 3: The Two Body Problem 22

The Anomalies

Satellite is at periapse

## True Anomaly = 0 deg

r
Mean Anomaly = 0 deg

The Anomalies

## Satellite is at = 80 deg e = 0.3

r
True Anomaly = 80 deg
E
Mean Anomaly = 48 deg

The Anomalies

## Satellite is at = 120 deg e = 0.3

r
True Anomaly = 120 deg
E
Mean Anomaly = 87 deg

## Lecture 3: The Two Body Problem 25

The Anomalies

Satellite is at apoapse

## True Anomaly = 180 deg

r
Mean Anomaly = 180 deg

The Anomalies

## The true anomaly advances quickly away from periapse

The eccentric anomaly is in between

## Beyond apoapse, its all in reverse (i.e., symmetric)

True anomaly advances the slowest away from apoapse
Eccentric anomaly is in between

The Anomalies

Lets see
some math!

## Lecture 3: The Two Body Problem (Vallado, 2013) 28

The Anomalies

True Anomaly
Note: c = a rp
Mean Anomaly = a a(1-e)
=ae
Eccentric Anomaly

## For a coordinate system centered on Earth, write the location of

the satellite in terms of E
X SAT = a cos E ae
2 2
X SAT YSAT
Eq. of Ellipse 2
+ 2 = 1 YSAT = b sin E
a b
Lecture 3: The Two Body Problem 29
Derivation of Keplers Equation

Now,
2 2 2 a 1 e2
r = XSAT + YSAT
= (a cos E ae)2 + (bsin E)2
= a 2 "#cos2 E 2ecos E + e2 + (1 e2 )sin 2 E \$%

## = a 2 "#1 2ecos E + e2 cos2 E \$%

2
= a 2 (1 ecos E ) r = a(1- ecos E)

## Now we will derive Keplers Equation

Lecture 3: The Two Body Problem 30
Derivation of Keplers Equation

p
Remember r =
1+ ecos
p (esin ) p ( esin ) r 2 hesin
r = 2
= =
(1+ ecos ) p2 p
But also r = a (1 ecos E )
r = aesin EE
hesin
So, aeE sin E =
p Note b sin E = r sin
he " b % b
aeE sin E = \$ sin E ' sin = sin E
p #r & r

## Lecture 3: The Two Body Problem 31

Derivation of Keplers Equation

p
Remember r =
1+ ecos
p (esin ) p ( esin ) r 2 hesin
r = 2
= =
(1+ ecos ) p2 p
But also r = a (1 ecos E )
r = aesin EE
hesin
So, aeE sin E =
p Note b sin E = r sin
he " b % b
aeE sin E = \$ sin E ' sin = sin E
p #r & r

## Lecture 3: The Two Body Problem 32

Derivation of Keplers Equation

rE =
hb
=
a (1 e 2
) a 1 e 2
h2
=p
Thus,
pa a(1 e 2 )a
3

rE =
a a (1 e ) 2

=
a 2
=

4
a 2 (1 e 2 ) a2 a

Thus, a(1 e cos E )E =
a
1
2

E e cos EE = 3 =n
a 2

## Integrating, E e sin E = nt + constant

Lecture 3: The Two Body Problem 33
Derivation of Keplers Equation

rE =
hb
=
a (1 e 2
) a 1 e 2
h2
=p
Thus,
pa a(1 e 2 )a
3

rE =
a a (1 e ) 2

=
a 2
=

4
a 2 (1 e 2 ) a2 a

Thus, a(1 e cos E )E =
a
1
2

E e cos EE = 3 =n
a 2

## Integrating, E e sin E = nt + constant

Lecture 3: The Two Body Problem 34
Derivation of Keplers Equation

rE =
hb
=
a (1 e 2
) a 1 e 2
h2
=p
Thus,
pa a(1 e 2 )a
3

rE =
a a (1 e ) 2

=
a 2
=

4
a 2 (1 e 2 ) a2 a

Thus, a(1 e cos E )E =
a
1
2

E e cos EE = 3 =n
a 2

## Integrating, E e sin E = nt + constant

Lecture 3: The Two Body Problem 35
Derivation of Keplers Equation

## If reference time is perigee, E = 0,

0 0
Et esin Et = nt p + constant constant = -nt p
p p

## Angle swept out at the M = Mean Anomaly

mean angular velocity,
n, the mean motion

M = n(t tp ) = E e sin E
Keplers Equation relates the Mean
Anomaly to the Eccentric Anomaly
Lecture 3: The Two Body Problem 36
Derivation of Keplers Equation

Anomaly?

## Yes! r = a(1 e cos E)

p
r=
1 + e cos
Useful Formula:
p a(1 e2 )
r = a(1 e cos E) = =
1 + e cos 1 + e cos
Lecture 3: The Two Body Problem 37
Conversions

## Any issues with these relationships?

M = n(t tp ) = E e sin E
p a(1 e2 )
r = a(1 e cos E) = =
1 + e cos 1 + e cos

## Quadrants! Two satellites with = 10 deg and =

-10 deg will be impossible to distinguish.
Lecture 3: The Two Body Problem 38

## (both and E are either 0 180 deg or 180 360 deg)

Lecture 3: The Two Body Problem 39

## Lecture 3: The Two Body Problem 40

If we have and need more:

If is given: p
r=
1 + e cos
r cos + ae
cos E =
a
r sin
sinE =
b
Solve E-e sin E = M for t (or M)
Lecture 3: The Two Body Problem 41
If we have t and need more:

## If t is given: M = n(t - tp)

Solve E-e sin E = M for E
r = a( 1-e cos E)
a cos E ae
and cos =
r
b
sin = sin E
r
2
a 1e
= sin E
Lecture 3: The Two Body Problem
r 42
Derivation of Keplers Equation

If t is given: If is given:
M = n(t - tp) p
Solve E-e sin E = M for E r=
1 + e cos
r = a( 1-e cos E) r cos + ae
cos E =
a cos E ae a
and cos =
r r sin
b sinE =
sin = sin E b
r
2
Solve E-e sin E = M for t (or M)
a 1e
= sin E
r

1+e E
Another Useful Relation: tan = tan
Lecture 3: The Two Body Problem
2 1e 2 43
Solving Keplers Equation

## Want to use Newton-Raphson Iteration.

Assume we want to solve f(y) = 0 for y.
Assume y = x+, where x is an approximate guess, and is a
small correction. Expanding in a Taylor Series:
f ""(x) 2
0 = f (y) = f (x + ) f (x) + f "(x) + +
2!
f(x)
Neglecting 2nd order terms and higher,
we can solve for : f(x0)
f (x)
=
f "(x)
x0 x
Lecture 3: The Two Body Problem 44
Solving Keplers Equation

## We need to iterate this since we have neglected higher order

terms: f (X )
Xn+1 = Xn + n = Xn n Iterate until n is
f "(Xn ) acceptably small
( = y-x)

## We want to solve E esin E = M f (E) = M E + esin E = 0

f '(E) = 1+ ecos E
So
M En + e sin En
E n +1 = En +
1 e cos En

## Lecture 3: The Two Body Problem 45

Summary

Today:
Keplers Laws
Properties of conic orbits
The Vis-Viva Equation! You will fall in love with this equation.
Converting between the anomalies

Monday:
Several examples of converting between the anomalies
Solving Keplers Problem
Satellite state representations

## Lecture 3: The Two Body Problem 46

Announcements
Homework #1 is due right now!
Either handed in or uploaded to D2L
Late policy is 10% per school day, where a day starts at
9:00 am.

## Lecture 3: The Two Body Problem 47

Derivation of Keplers Equation
cos E e a (cos E e )
So, cos = =
1 + e cos E r
2 2
2 1 e sin E a 1 e sin E
sin = 1 cos = =
1 + e cos E r
cos E e
1
2 1 cos
1 e cos E 1 e cos E cos E + e
tan = = =
2 1 + cos cos E e 1 e cos E + cos E e
1+
1 e cos E
(1 + e )(1 cos E ) 1 + e 2 E
= = tan
(1 e )(1 + cos E ) 1 e 2

1+ e E
tan = tan
2 1e 2
Lecture 3: The Two Body Problem 48